ADAPTATIONS OF DECAPOD CRUSTACEANS TO LIFE IN MANGROVE SWAMPS - Malley, D. F. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Decapod crustaceans such as sesarmid and ocypodid crabs and thalassinid lobsters are conspicuous in numbers and bio mass on the mangrove swamp floor. An understanding of their biology and physiology is concomitant with a full understanding of their role in swamp ecology and management and for controlling them when they are pests or for augmenting their usefulness. The swamp environment of decapods is essentially a moist, low oxygen (in standing water), very broad intertidal habitat with an abundant food source available in angiosperm tissue. Present knowledge of the biology of mangrove decapods will be briefly summarized, such as feeding, respiratory, reproductive and behavioural adaptations, and including reports on feeding by Chiromanthes spp. in Malaysian swamps. In addition, the paper will attempt to identify fruitful areas for physiological and ecological research such as metabolic adaptations to angiosperm diet.